COMMUNICATING IN THE VERNACULAR: DIGITAL TYPE AND DESIGN IN TAMIL CINEMA ADVERTISING (Proceeding of the International Conference on Arts and Humanities, 2018)
Typography is defined as ‘the arrangement and appearance of printed matter’. However, in today’s context it can be updated to include the design arrangement of any communicative material.  ‘Grammatology’ according to Jacques Derrida, is the study of writing as a distinctive form of representation and within its domain are the material forms and processes of typography and design. Typography, in relation to structuralist theory, as instituted by type designers Bodoni and Didot charts a shift from the humanist understanding of printed letters as reflections of handwritten marks or classical proportions towards the modernist view of typography as the endless manipulation of abstract elements.  It is possible to draw parallels with modern English typography and similar stylistic developments in the title designs for Tamil cinema posters and hoardings where words, images, and objects participate in a culturally determined meaning characterizing a verbal language. Though cinema in India has been in existence for over a hundred years, in recent years there has been an explosion of new and highly inventive typefaces. This paper will examine how digital typography and design as a vernacular cultural force sought to reach a varied audience in the titles created for Tamil cinema publicity from the year 2000 onwards. The designer developed visual codes that forced the audience to reevaluate conventional Tamil typeface design. While earlier Tamil cinema advertising used handcrafted type and imagery to promote the film, it changed with digital technology enabling the typographic design of the titles of the films to indicate the genre be it mythological, historical, patriotic, romantic or action oriented.
Keywords: Typography; Design; Vernacular; Visual Code